If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 4 = 9 + 12x Reorder the terms: 4 + 11x = 9 + 12x Solving 4 + 11x = 9 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 4 + 11x + -12x = 9 + 12x + -12x Combine like terms: 11x + -12x = -1x 4 + -1x = 9 + 12x + -12x Combine like terms: 12x + -12x = 0 4 + -1x = 9 + 0 4 + -1x = 9 Add '-4' to each side of the equation. 4 + -4 + -1x = 9 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 9 + -4 -1x = 9 + -4 Combine like terms: 9 + -4 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5
| -10y+8x=9 | | 1x^4-7x^3+11x^2-5x=0 | | dy/dx=1/2nu | | s-14=24 | | 8x-10y=9 | | 52=66-p | | 54=62-z | | k-45=22 | | 25/4=75/m | | (x+2)(.75)=27 | | 35=50-n | | 43=w-22 | | 2a+2a-a-a+3a= | | 9.8x^2-10x-50=0 | | 29-4x=8-7x | | 32=h-5 | | 93-k=20 | | ln(2x+1)=(x-4) | | 31=b-16 | | 17=61-a | | j-51=21 | | x+1+2x=5x+3 | | 79=97-r | | 48=76-n | | 52=69-x | | (0.3213-2x/x)^2=10 | | 55-c=14 | | 0=16(t^2-5t-6) | | u-80=19 | | m-4=52 | | 64=68-a | | 3x+8=-18 |